Simulating the immune inspired energy charging mechanism for swarm robotic systems - Al Haek, Mohammed; Ismail, Amelia Ritahani (Asian Research Publishing Network, 2017)
Fault tolerance or the property that enables a system to continue its operation properly in the event of partial failure is one of the most desired criteria in swarm robotic systems. There is a possibility that a continuous failure of the member(s) of the swarm, will reflect on the overall performance of the systems. In this paper, we proposed an immune-inspired energy charging mechanism, which is inspired by the process of immune responses. The proposed energy charging mechanism is presented, simulated and compared with another common energy charging mechanism, which is the use of contact-less energy charging area. Based on the experimental results, the proposed mechanism shows an improvement in terms of performance time and aggregate energy of the swarm to perform its task.